THE IMPLEMENTATION OF EXTENSIVE READING PRINCIPLES IN AN EXTENSIVE READING CLASS: STUDENTS’ PERCEPTIONS - Monika Andita Argha Puspa; Debora Tri Ragawanti (ETERNAL (English Teaching Journal), 2022)
For running a successful extensive reading (ER) program, Day and Bamford’s ten ER priciples becomes “key ingredients” (Ng, Renandya, and Chong, 2019. P. 172). This study is aimed at revealing EFL students’ perceptions toward the use of the ER principles in their ER class. To achieve the aim, a questionnaire was distributed to 39 students from English Language Education Program, Universitas Kristen Satya Wacana. Besides, an interview to 10 student-respondents was also conducted. The collected data was then analyzed by classifying them under several themes, creating descriptive statistics, and extracting transcripts of the interviews. The results revealed that EFL student-participants agree that the ER course has applied all ten ER principles. How the ER principles were employed in the course and how they could enhance both students’ linguistic and nonlinguistic competences are also discussed in this paper.